Aberrant right subclavian artery: A review - Ilayakumar Paramasivam, Mch; Sritharan Narayanan, Mch; B.Vella Duraichi, Mch; Jayachander Kulandaivelu, Mch; Sasikumar Ravichandran, MS; M. Ramya Vivek, Mch; Harishkumar Ayyavoo, Mch (JVS-Vascular Insights, 2025)
Aberrant subclavian artery is a rare condition, with patients often present with dysphagia, dyspnea, back pain, or upper limb ischemia; occasionally, the condition is incidentally discovered as a mediastinal mass on chest radiography. Currently, no consensus exists on the management of aberrant right subclavian artery, which includes open surgery, hybrid repair, and endovascular intervention, depending on the surgeon's preference and expertise. Despite the lack of a uniform treatment approach, consistently good outcomes have been reported. We describe a case of an aberrant right subclavian artery with a Kommerell diverticulum that presented with dysphagia and was treated with open surgical repair, followed by a review of the literature.